Bearing habit and production of pears grafted onto different rootstocks - Pasa, Mateus da Silveira; Fachinello, José Carlos; Schmitz, Juliano Dutra; de Souza, André Luiz Kulkamp; Herter, Flavio Gilberto (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this research was to evaluate the bearing habit and yield of pear cultivars (Pyrus communis) grafted onto quince (Cydonia oblonga) and callery pear (P. calleryana) rootstocks. The experiment was carried out in the winter of 2009 and 2010, in a pear orchard conducted as central leader, at 1.0x5.0 m spacing, with three pear cultivars (Carrick, Packham, and Williams) combined with one callery pear (Clone D6 of P. calleryana) and 15 quince rootstocks. The following variables were assessed: percentage of vegetative spurs, reproductive spurs, vegetative brindles, reproductive brindles and bourses; total number of flower buds; yield per plant; and productive efficiency. Bearing habit of pear cultivars is influenced by the rootstocks, mainly for reproductive spur formation. In general, there was an inverse relationship between the percentage of vegetative and reproductive spurs, and between productive efficiency and vigor for all scion and rootstock combinations. In order to enhance production, cultural management in orchards of the evaluated cultivars, especially on pruning, should be oriented according to the rootstock used and to the bearing habit of each combination.